PENGARUH PELATIHAN DAN PENGALAMAN KERJA TERHADAP PROFESIONALISME GURU DI SMP NEGERI KECAMATAN PEMANGKAT - Neri Wahyuni; Aunurrahman Aunurrahman; Wahyudi Wahyudi (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe teacher professionalism, teacher training, and teacher workexperience at SMP Negeri Kecamatan Pemangkat. It also aims to determine the effect oftraining and work experience on the teacher professionalism at SMP Negeri KecamatanPemangkat. The form of this research is quantitative research with correlationaltechniques. This study was conducted to examine the relationship between theindependent variable and the dependent variable. The independent variables in this studywere training (X1) and work experience (X2), while the dependent variable was teacherprofessionalism (Y). The population in this study were teachers at SMP NegeriKecamatan Pemangkat. The number of samples in this study were 69 teachers. Datacollection instruments used were questionnaire. The results of data processing showedthat the teachers professionalism in SMP Negeri Kecamatan Pemangkat is low, teachertraining in SMP Negeri Kecamatan Pemangkat is low, and the work experience in SMPNegeri Kecamatan Pemangkat is very low. It also showed that training and workexperience simultaneously have an effect of 26.10% on the teachers professionalism atSMP Negeri Kecamatan Pemangkat. This means that teacher training and workexperience simultaneously have a positive effect on increasing teacher professionalism.Keywords: Theacher Professionalism, Teacher Training, Teacher Work Experience